Pore Pressure Responses of Liquefied Numerical Sand Columns - Widjojo Prakoso; Dheya Mazaya; Rumaisha A. Kartika (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2022)
The Palu 28 September 2021 M 7.5 Earthquake has brought several new challenges to the understanding of liquefaction and its following geotechnical phenomena. In addition, that main shock was followed by a series of aftershocks within a short time frame. The common geotechnical conditions of Palu area include layered soils conditions, and the associated variability of geotechnical conditions exists. This paper reports the dynamic effective stress analysis (ESA) study of four different liquefiable layered sand columns, and the above three conditions (layered soils, variability, aftershocks) are explicitly modeled. The dynamic ESA employs the PM4Sand constitutive model for liquefiable sands, implemented in the OpenSees platform. Three ground motion sets (“main shock only”, “main shock plus aftershock”, “aftershock” only) of variable amplitude, single frequency harmonic motions are used. The models are validated by comparing qualitatively their results against laboratory test results and field measurements. The saturated sand layers in all cases subjected to “main shock only” are liquefied with different detailed excess pore pressure (EPP) responses, highlighting the importance of the system response of liquefying sand columns. The cases subjected to “main shock plus aftershock” show a much a longer higher EPP state, while cases subjected to both “main shock plus aftershock” and “aftershock only” indicate a longer liquefaction state during the aftershock. The implication of the longer duration in the higher EPP state and the longer liquefaction state is that a longer duration of lower shear strength conditions would exist. The different EPP responses resulted from different geotechnical conditions represented by the four sand columns suggest that the variability of geotechnical conditions would have an important influence on the system response.